On the Intentionality of Cultural Products: Representations of Black History As Psychological Affordances - Salter, Phia S.; Adams, Glenn (Frontiers in Psychology, 2016)
A cultural-psychological analysis emphasizes the intentionality of everyday worlds: the idea that material products not only bear psychological traces of culturally constituted beliefs and desires, but also subsequently afford and promote culturally consistent understandings and actions. We applied this conceptual framework of mutual constitution in a research project using quantitative and qualitative approaches to understand the dynamic resonance between sociocultural variance in Black History Month (BHM) representations and the reproduction of racial inequality in the U.S. In studies 1 and 2, we considered whether mainstream BHM artifacts reflect the preferences and understandings of White Americans (i.e., psychological constitution of cultural worlds). Consistent with the psychological constitution hypothesis, White American participants reported more positive affect, better recognition, and greater liking for BHM representations from the schools where White Americans were the majority than BHM representations from the schools where Black students and other students of color were the majority. Moreover, as an indication of the identity relevance of BHM representations, White identification was more positively associated with judgments of positive affect and preference in response to BHM representations from White schools than BHM representations from the schools where Black students were in the majority. In studies 3 and 4, we considered whether BHM representations from different settings differentially afford support or opposition to anti-racism policies (i.e., cultural constitution of psychological experience). In support of the cultural constitution hypothesis, BHM representations typical of schools where Black students were in the majority were more effective at promoting support for anti-racism policies compared to BHM representations typical of predominately White schools and a control condition. This effect was mediated by the effect of (different) BHM representations on perception of racism. Together, these studies suggest that representations of Black History constitute cultural affordances that, depending on their source, can promote (or impede) perception of racism and anti-racism efforts. This research contributes to an emerging body of work examining the bidirectional, psychological importance of cultural products. We discuss implications for theorizing collective manifestations of mind.